Design and Dynamic Modelling of a Hybrid Power System for a House in Nigeria - Lawrence O. Aghenta; M. Tariq Iqbal (International Journal of Photoenergy)
This paper presents the design and dynamic modelling of a hybrid power system for a house in Nigeria. Thermal modelling of the house under consideration is carried out using BEopt software to accurately study the heat loss through the walls, windows, doors, and roof of the house. The analysis of this thermal model is used to determine hourly load data. Design of an optimum hybrid power system for the house is done with HOMER Pro software. The hybrid power system is made up of a diesel generator and a stand-alone PV system. The proposed PV system consists of PV arrays, DC–DC boost converter, MPPT controller, single-phase full-bridge inverter, inverter voltage mode controller (PI controller), and single-phase step-up transformer. Dynamic simulation of the proposed PV system component of the hybrid power system is carried out in MATLAB/Simulink environment to study the power quality, harmonics, load impact, voltage transients, etc. of the system, and the simulation results are presented in the paper.